What prima philosophia in 21st century? - Paruzel, Mariola; Makuła, Szymon (Folia Philosophica, 2010)
Report from the conference “What is ‘prima philosophia’ in the 21st century?”, which took place on May 5-6, 2009, in Katowice. The conference was organized by the Philosophers' Scientific Circle at the Institute of Philosophy of the Faculty of Social Sciences of the University of Silesia in Katowice.